2017
DOI: 10.1016/j.bbadis.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Sodium restriction modulates innate immunity and prevents cardiac remodeling in a rat model of metabolic syndrome

Abstract: In the view of the relationships between excessive sodium intake, immunity and target organ damage, we hypothesized that reduction in dietary sodium would be beneficial in the prevention of cardiac alterations through a restrained local immunity response in a rat model of metabolic syndrome. Sprague-Dawley rats were fed a 60% fructose diet with either a normal sodium (0.64% NaCl) or a low sodium content (<0.01% NaCl) for 8weeks. After 4weeks, rats were infused or not with angiotensin II (200ng·kg·min, sc) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…15). Consistent with other reports [48,49], the percentages of fibrosis area in the hearts from saline-treated Rit1 +/+ and Rit1 A57G/+ mice were higher (0.41 ± 0.10 and 0.59 ± 0.10, respectively) (Fig. 4c), than those in non-treated Rit1 +/+ and Rit1 A57G/+ mice (0.17 ± 0.04 and 0.38 ± 0.04) (Fig.…”
Section: Resultssupporting
confidence: 94%
“…15). Consistent with other reports [48,49], the percentages of fibrosis area in the hearts from saline-treated Rit1 +/+ and Rit1 A57G/+ mice were higher (0.41 ± 0.10 and 0.59 ± 0.10, respectively) (Fig. 4c), than those in non-treated Rit1 +/+ and Rit1 A57G/+ mice (0.17 ± 0.04 and 0.38 ± 0.04) (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Lower heart weight/body weight index was observed in group HFFD 5+3, and the administration of venlafaxine caused a decrease in heart weight independently from the length of HFFD. Other studies showed that in animal models of metabolic syndrome, with a high fructose diet, abnormalities in myocardial structure (Cheng et al, 2014) and cardiac hypertrophy were present (Delbosc et al, 2005;Jover et al, 2017). Due to a high intake of fat and fructose, hepatic and intracardial lipid accumulation was previously observed, which could affect not only morphology but also the function of the organs.…”
Section: Discussionmentioning
confidence: 98%